2018
DOI: 10.1002/da.22764
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia mediates the longitudinal relationship between anxiety and depressive symptoms in a nationally representative sample of adolescents

Abstract: Findings suggest that anxiety may increase risk for the development of later depression through insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 83 publications
(102 reference statements)
1
12
0
1
Order By: Relevance
“…Likewise, other bridge mental states or symptoms need to be investigated as well. Currently, only two bridge mental states were assessed, while there are many other symptoms (e.g., insomnia [84]), behaviors (e.g., avoidance behaviors [85]), or cognitive processes (e.g., attributional styles [86]) that have previously been identified as shared features of depressive and anxiety disorders. Ideally, complex constructs like avoidance behavior or repetitive negative thinking would be measured using multiple items.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other bridge mental states or symptoms need to be investigated as well. Currently, only two bridge mental states were assessed, while there are many other symptoms (e.g., insomnia [84]), behaviors (e.g., avoidance behaviors [85]), or cognitive processes (e.g., attributional styles [86]) that have previously been identified as shared features of depressive and anxiety disorders. Ideally, complex constructs like avoidance behavior or repetitive negative thinking would be measured using multiple items.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, meta-analytic research on adolescent insomnia suggests that insomnia is a precursor to depressive symptoms, and not vice versa (Lovato and Gradisar, 2014). Recent research on adolescents has confirmed a pathway from anxiety to depression through insomnia (Li et al, 2018b), although this study grouped types of insomnia together. Longitudinal research that examines the mechanistic progression of these disorders would greatly increase understanding of why certain sleep problems are associated with symptoms of depression and anxiety.…”
Section: Discussionmentioning
confidence: 84%
“…[ 7 ] When the body is in a state of tension and anxiety for a long time, the sensory function of the nervous system will be extremely sensitive, causing difficulty in falling asleep, easy to wake up, aggravating sleep disorders, forming a vicious circle. [ 8 , 9 ] Research using resting-state functional magnetic resonance imaging (rs-fMRI) suggests that insomnia is related to arousal, emotion, reward, and abnormal functional activities in cognitive brain regions. [ 10 , 11 ] It is not only related to functional abnormalities in local brain regions, but also related to abnormal internal connections of default network, prominence network, and emotional network.…”
Section: Introductionmentioning
confidence: 99%